A Digital-Based Assessment Model Integrating Religious Character Values in Islamic Religious Education: Toward Decolonizing Islamic Studies - Santi Lisnawati; Eva Dwi Kumalasari; Bahrum Subagiya; Mas’udin Syarifuddin (Jurnal Pendidikan Islam, 2026)
The rapid expansion of digital assessment in higher education creates opportunities for improving learning evaluation, yet it raises concerns about how assessment can measure academic competence while also cultivating moral and religious character in Islamic education. This study aims to develop a digital-based assessment model that integrates religious character values in evaluating classroom action research proposal writing in Islamic Religious Education courses. The study employed a Research and Development (R&D) approach using the ADDIE framework, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through surveys, interviews, expert validation, proposal writing assessments, and student feedback questionnaires. The results of the needs analysis indicate limited use of digital assessment and minimal integration of religious character values in existing evaluation practices. The developed assessment rubric integrates research competence indicators with religious character values such as honesty, responsibility, sincerity, consistency, and humility. Expert validation using Aiken’s V demonstrates high content validity, while implementation with prospective Islamic Religious Education teachers shows that the model is effective in improving research proposal writing skills and fostering academic integrity. The study concludes that integrating digital assessment with Islamic character values provides a holistic evaluation framework that supports both professional competence and ethical development in Islamic higher education.